Effectiveness of non-invasive respiratory support strategies in patients with COVID-19: A systematic review and meta analysis. (December 2022) - Kumar, Vinesh; Malik, Umair Arshad; Kumari, Reshman; Berkha,; Kumar, Vijay; Kumar, Manoj; Simran,; Suman,; Nasim, Bushra
Abstract: Background: BackgroundThe effectiveness of non-invasive respiratory strategies, namely CPAP and HFNO, in reducing the risk of mortality and tracheal intubation in patients with severe COVID-19 is not well established. Methods: A thorough literature search was conducted across 3 electronic databases (Medline, EMBASE and Cochrane Central) from inception through July 2022. Randomized controlled trials (RCTs) and observational studies assessing the impact of CPAP or HFNO on clinical outcomes in patients infected with COVID-19 were considered for inclusion. End-points included all-cause mortality and risk of tracheal intubation. Evaluations were reported as risk ratios (RRs) with 95% confidence intervals (CI) and analysis was performed using a random effects model. I 2 index was used to assess heterogeneity. Results: From the 1041 articles retrieved from initial search, 7 potentially relevant studies (n = 2831 patients) were included in the final analysis. Compared to conventional oxygen therapy, non-invasive respiratory strategies reduced the risk of tracheal intubation (RR = 0.84, [95% CI 0.72, 0.98]; p = 0.02, I 2 = 43%) and all-cause mortality (RR = 0.83, [95% CI 0.71–0.97]; p = 0.02, I 2 = 0%) in patients infected with COVID-19 However, reduction in length of hospital stay was not significant between the non-invasive respiratory group and conventional oxygen therapy (MD = −0.60, [95% CI -2.17 – 0.98]; p = 0.46, I 2 = 26%). Conclusion: This meta-analysis supports the application of non-invasive respiratory strategy is feasible as it can delay the start of tracheal intubation and reduce mortality rates among patients infected with COVID-19. Highlights: Data indicate that high-flow oxygen treatment may reduce the requirement for endotracheal intubation but not death rates. Significant variation exists in guidelines regarding the use of non-invasive respiratory strategies in COVID-19 patients. Randomized controlled trials to assess the benefits of non-invasive respiratory support strategies among COVID-19 patients.